Investigation of an Innovative “Cotton Hollow” Yarn - Andrysiak, Jerzy; Sikorski, Krzysztof; Wilk, Edward; Matusiak, Małgorzata (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
Cotton is a basic raw material processed in the textile industry all over the world. Some new cotton products have been developed thanks to the inventions and efforts of scientists and engineers dealing with cotton. One of the innovative cotton products is SPINAIR yarn by Kurabo (Japan). It is so called “hollow” yarn made of cotton and PVA fibres. PVA fibres are introduced into the yarn during the spinning process. Next they are dissolved and removed in fabric finishing, thanks to which in the final product the yarn is composed only of cotton fibres. The yarn has been developed to improve the thermal insulation of cotton fabrics. Due to the dissolving of PVA fibres, the structure of yarn and fabrics made of it is loose and porous. The air trapped inside the yarn between the cotton fibres increases the thermal resistance of fabrics. Within the framework of the work presented composite “hollow” yarn 42 tex made of cotton (80%) and modified PVA (Polyvinyl alcohol) fibres (20%) was investigated within the range of its structural, mechanical and technological parameters. Woven fabric was then manufactured with the application of the 42 tex CO80/ PVA20 yarn in the weft direction. Investigation of the manufactured woven fabric with Alambeta confirmed that fabric with weft yarn 42 tex CO80/PVA20 is characterised by a higher thermal resistance and warmer sensation while touching than that made of 42 tex cotton rotor yarn in the weft.
Keywords: “hollow” yarn; cotton; woven fabrics; thermal resistance; thermal comfort